2017
DOI: 10.1002/adfm.201700728
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Piezoelectric Touch Sensor by Alignment of Lead‐Free Alkaline Niobate Microcubes in PDMS

Abstract: This state-of-the-art value outperforms bulk piezoelectric ceramics and composites with randomly dispersed particles, and is comparable to the values reported for the piezoelectric polymers PVDF and P(VDF-TrFE). Optimized composite films are incorporated in flexible piezoelectric touch sensors. The high sensitivity is analyzed and discussed. As the fabrication technology is straightforward and easy to implement, applications are foreseen in flexible electronics such wireless sensor networks and biodiagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 32 publications
2
68
0
Order By: Relevance
“…[64] Copyright 2015, Elsevier. example, under an excitation of 5 N, the voltage remains steady at 16 V. [67] The results demonstrate an open-circuit voltage output larger than those of PVDF and ceramic PZT. A flexible electronic-skin sensor capable of detecting human physiological signals such as wrist pulse, muscle movements, speaking for voice recognition, and disease diagnosis was presented.…”
Section: Piezoelectric Polymer-based Energy Harvestersmentioning
confidence: 76%
See 1 more Smart Citation
“…[64] Copyright 2015, Elsevier. example, under an excitation of 5 N, the voltage remains steady at 16 V. [67] The results demonstrate an open-circuit voltage output larger than those of PVDF and ceramic PZT. A flexible electronic-skin sensor capable of detecting human physiological signals such as wrist pulse, muscle movements, speaking for voice recognition, and disease diagnosis was presented.…”
Section: Piezoelectric Polymer-based Energy Harvestersmentioning
confidence: 76%
“…Films with 1.1 mm of thickness were used with an excitation force variation from 1, 3, and 10 N peak to peak. As an example, under an excitation of 5 N, the voltage remains steady at 16 V . The results demonstrate an open‐circuit voltage output larger than those of PVDF and ceramic PZT.…”
Section: Representative Energy‐harvesting Applicationsmentioning
confidence: 88%
“…A typical piezoelectric sensor has three types of sensing modes, that is, longitudinal (d 33 ), transverse (d 31 ), and shear (d 15 ), depending on the way a piezoelectric material is cut or polarized. It is relatively easy to produce either longitudinal or transverse sensors based flexible piezoelectric [59,60] since the same electrode can be used for poling and sensing operations. However, the design and manufacture of shear force sensors continues to be a challenge as it requires a more complex configuration or device structure since the electrodes are applied normal to the direction of polarization.…”
Section: Self-powered Piezoelectric Sensorsmentioning
confidence: 99%
“…For sensor applications, on the other hand, the figure of merit is d 33 /ε, where ε is the absolute dielectric constant, or permittivity. Here, composites have shown to have the upper hand due to their low value of ε [11][12][13]. For energy harvesting, with the figure of merit being d 33 2 /ε, recent studies have shown that composites and ceramics can perform equally well [14,15].…”
Section: Introductionmentioning
confidence: 99%